“From the East, This Town Borders the River Zbruch Bordering Poland...”. Towns in the Galicia, Volhynia and Podolia Borderland in the Late 18th Century: Urban, Public, Political, and Socio-Economic Spaces - Kargol, Tomasz; Ślusarek, Krzysztof (Studia Historiae Oeconomicae, 2018)
“From the East, This Town Borders the River Zbruch Bordering Poland...”. Towns in the Galicia, Volhynia and Podolia Borderland in the Late 18th Century: Urban, Public, Political, and Socio-Economic Spaces